Multilevel Constitutionalism In Mexico In Human Rights Matters (A National Shield) - Tapia Hernández, Erick Francisco (Universidad Hemisferios, 2024)
The main objective of this research is to identify the fair dimension of Multilevel Constitutionalism in Mexico in terms of the protection of human rights; for this purpose, the deductive, inductive, dialogic and exegetical method will be used in an enunciative and non-limiting manner. We will find as a main result that the legislation in Mexico seeks to avoid the interference of supra and subnational bodies in the protection of Human Rights, to conclude after a detailed study of the above, that in Mexico there is a legal shield so that, to the extent of as far as possible, the Judicial Branch of the Federation is the one who primarily issues resolutions and criteria on human rights, without taking into consideration external opinions, which it has achieved by issuing its own criteria, which limit the competence of other national and international bodies that could resolve controversies on the matter.